Implementasi Pemikiran Hermeneutika Jacques Derrida dalam Memahami Hadis Nabi SAW: Implementation of Jacques Derrida's Hermeneutic Thought in Understanding the Hadith of the Prophet SAW - Shobri, Alwi; Masruhan, Masruhan; Hasbulloh, Moh (Undiksha, 2025)
Jacques Derrida’s hermeneutical thought offers an innovative a methodological framework for interpreting the hadith of the Prophet Muhammad. Through the lens of deconstruction, Derrida posits that the meaning of texts must always be questioned and revised, thus preventing texts from ever reaching stability or final truth. In the context of the Prophet’s hadith, a deconstructive approach is necessary to open up a more dynamic and contextual space for interpretation. One of its applications is to break the stagnation or rigidity in the interpretation of hadith texts, which are often understood only literally. This study will present Jacques Derrida’s hermeneutical thought and its application in interpreting the hadith of the Prophet Muhammad SAW. The article employs a descriptive-analytical library research study with a hermeneutic approach, examining how Derrida’s hermeneutical thought can be applied to understanding the hadith texts. This writing is expected to expand the dimensions and horizons of interpretation with a critical and contextual perspective. For example, the prophetic tradition regarding the origin of woman from man’s rib, often understood literally, can be deconstructed to reveal its deeper symbolic meaning.